Chapter 1 Family Companies and Family Constitutions: Historical and Comparative Perspectives - Holger Fleischer (Emerald Publishing Limited, 2023)
This chapter provides an introduction to the world of family companies and family constitutions from a legal perspective. It first studies the legal types of business organizations that family firms have chosen across time and jurisdictions. It then illustrates how early predecessors of family constitutions evolved in the late Middle Ages and what modern family constitutions look like in different countries today. Further considerations are devoted to the governance framework of family firms. The chapter concludes by exploring the potential legal effects of family constitutions under German company and contract law.
10.1108/978-1-83797-200-520231001; 10.1108/978-1-83797-200-520231001; Family Firms and Family Constitution; EBP099697173